Lutheran conceptions of human dignity in a global context: A conversation with Indian Dalits and European/Americans. Issue 4 (24th September 2020) - Ronnevik, Andrew
Abstract: This paper explores Lutheran conceptions of human dignity expressed by European/Americans (Oswald Bayer and John Witte, Jr.) and Dalits (Raj Bharath Patta and Surekha Nelavala). The former emphasize the human coram Deo, the lost dignity of the individual sinner, and the imputed dignity of the justified. The latter attend especially to humans coram hominibus, the dignity of the "sinned upon" in Indian society, and the full inclusion of Dalits. While neither view replaces the other, I argue that European/Americans must become more responsive to differentiated social realities in which persons are "sinful" and "sinned upon" in unequal ways.